2018
DOI: 10.1039/c8ra01385c
|View full text |Cite
|
Sign up to set email alerts
|

An amperometric glucose biosensor based on PEDOT nanofibers

Abstract: Here we present a simple, low cost approach for the production of PEDOT nanofiber biosensors using simple techniques. Firstly, nanofibers of PEDOT were produced by the chemical vapor polymerization of EDOT on FeCl 3 containing electrospun PAN nanofiber mats. The nanofibers were characterized by SEM, FTIR, CV and conductivity studies, which indicated the formation of homogeneous, porous, electroactive PEDOT nanofibers. The fabrication of biosensors was achieved through the loading of various amounts of GOx on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 47 publications
(49 reference statements)
0
33
0
Order By: Relevance
“…In Figure 2 we present the FTIR spectrum of the different reagents used to synthesize the AEMs before and after modification. First, the spectrum of PECH and PAN are presented with their principal peaks [53,54] (panels a and b), followed by the synthesized AEM in panel c. The three characteristic peaks verify the proper crosslinking of the polymers above the first peak, derived from the PECH, corresponds to the OH group at 3378 cm −1 ; the second peak, at 2242 cm −1 belongs to the C-N of the PAN polymer; lastly, the third peak at 1640 cm −1 is associated with the C-N group that also corresponds to the PECH polymer [39]. This membrane was superficially modified immersing it alternately in PEI and GA solutions.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In Figure 2 we present the FTIR spectrum of the different reagents used to synthesize the AEMs before and after modification. First, the spectrum of PECH and PAN are presented with their principal peaks [53,54] (panels a and b), followed by the synthesized AEM in panel c. The three characteristic peaks verify the proper crosslinking of the polymers above the first peak, derived from the PECH, corresponds to the OH group at 3378 cm −1 ; the second peak, at 2242 cm −1 belongs to the C-N of the PAN polymer; lastly, the third peak at 1640 cm −1 is associated with the C-N group that also corresponds to the PECH polymer [39]. This membrane was superficially modified immersing it alternately in PEI and GA solutions.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Notably, the direct electrodeposition of composite nanomaterials has been preferred for realizing the high conductivity and synergistic effect between the composite materials for biosensing applications. However, to explore the Copyright 2018 Elsevier) polymerization of EDOT and deposited it onto an electrode surface by electrospinning followed by GOx loading in various amounts [265]. This study showed that the excessive GOx loading on PEDOT nanofibers had an adverse effect on response time due to excessive swelling of the PEDOT matrix.…”
Section: Electrochemical Depositionmentioning
confidence: 98%
“…However, for biomedical applications, their use is limited mainly because of their poor processability and mechanical properties [36]. The doping of these polymers with long chains can overcome these limitations although it can affect the conductivity of the resulting materials [34,42]. Another solution is to blend the intrinsic conductive polymer with another polymer possessing easier processability in order to obtain a composite with improved mechanical and biocompatibility properties [30].…”
Section: Electroactive Conductive Polymersmentioning
confidence: 99%